Betawi Traditional Culinary; Reflection The History Of Jakarta (Formerly Known As Batavia) - UNTARI, Dhian Tyas; AVENZORA, Ricky; DARUSMAN, Dudung; PRIHATNO, Joko; ARIEF, Harnios (Journal of Economic Development, Environment and People, 2017)
Abstract. Betawi is a native of Jakarta where once known as Batavia. The concept of modern society in Jakarta, shifting the traditional value of Betawi. So it is important to study about Betawi culinary; as a Betawi cultural product. Research have the Two phases. The first phase to analyzing the potentials and the functions of Betawi Traditional Cuisines; have using secondary data and the second is to analyzing as well as testing the culinary socio-cultural representation in the community of the Special Capital District of Jakarta using the primary data. Geographically, the respondents will be taken from the five administrative areas of the Special Capital District of Jakarta (330 respondents in total). The assessment aspects in the representation test include; knowledge, uniqueness, originality, social value, distribution, sensitivity and seasonality